Drivers and demographic consequences of seasonal mass changes in an alpine ungulate. Issue 3 (12th February 2018) - Douhard, Mathieu; Guillemette, Simon; Festa‐Bianchet, Marco; Pelletier, Fanie
Abstract: We know little about the determinants and demographic consequences of the marked seasonal mass changes exhibited by many northern and alpine mammals. We analysed 43 years of data on individual winter mass loss (the difference between mass in early June and mass in mid‐September the previous year) and summer mass gain (the difference between mass in mid‐September and in early June of the same year) in adult bighorn sheep ( Ovis canadensis ). We calculated relative seasonal mass change as a proportion of individual body mass at the start of each season. We first examined the effects of weather and population density on relative changes in body mass. We then assessed the consequences of relative seasonal mass changes on reproduction. Mean April–May temperature was the main driver of relative seasonal mass changes: warm springs reduced both relative winter mass loss and summer mass gain of both sexes, likely partially due to a trade‐off between growth rate of plants and duration of access to high‐quality forage. Because these effects cancelled each other, spring temperature did not influence mass in mid‐September. Mothers that lost relatively more mass during the winter had lambs that gained less mass during summer, likely because these females allocated fewer resources to lactation. Winter survival of lambs increased with their summer mass gain. In males, relative mass loss during winter, which includes the rut, did not influence the probability of siring at least one lamb, possibly indicating that greater mating effort did not necessarily translate into greater reproductive success. Our findings improve our understanding of how weather influences recruitment and underline the importance of cryptic mechanisms behind the effects of climate change on demographic traits.